Bridging the immunogenicity of a tetravalent dengue vaccine (TAK-003) from children and adolescents to adults - Inge LeFevre; Lulu Bravo; Nicolas Folschweiller; Eduardo Lopez Medina; Edson Duarte Moreira; Francesco Nordio; Mayuri Sharma; Leslie M. Tharenos; Vianney Tricou; Veerachai Watanaveeradej; Peter J. Winkle; Shibadas Biswal (npj Vaccines, 2023)
Abstract Immunobridging is an important methodology that can be used to extrapolate vaccine efficacy estimates to populations not evaluated in clinical studies, and that has been successfully used in developing many vaccines. Dengue, caused by a mosquito-transmitted flavivirus endemic to many tropical and subtropical regions, is traditionally thought of as a pediatric disease but is now a global threat to both children and adults. We bridged immunogenicity data from a phase 3 efficacy study of a tetravalent dengue vaccine (TAK-003), performed in children and adolescents living in endemic areas, with an immunogenicity study in adults in non-endemic areas. Neutralizing antibody responses were comparable in both studies following receipt of a two-dose TAK-003 schedule (months 0 and 3). Similar immune responses were observed across exploratory assessments of additional humoral responses. These data support the potential for clinical efficacy of TAK-003 in adults.